Peran Artificial Intelligence dalam Meningkatkan Akurasi Shade Guide di Kedokteran Gigi Estetik - Octarina; Nurkhansa Putri, Aisyah; Yuliani Taramalinda, Elizabeth; Rani Rahayu, Elma; Rainy Soenoe, Hanna; Safa Haniyah, Indira; Ardena Lianto Lie, Melisa (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Background: Accurate tooth shade selection is a challenge in esthetic dentistry due to the subjectivity of visual methods and their sensitivity to environmental factors. Objectives: To examine the role of Artificial Intelligence (AI) in improving accuracy and the development of AI-based shade guide systems for tooth color determination. Methods: A literature review was conducted using data from several related studies. Results: AI and digital technology improve the accuracy and consistency of shade matching compared to conventional visual techniques. Deep learning models such as CNN, YOLO, and SegNet/U-Net enhance the precision of the process. AI also shortens clinical time and reduces dependence on human perception. However, its implementation faces challenges, including high costs, the need for large, high-quality datasets, and ethical concerns such as data privacy and informed consent. Conclusion: AI-assisted shade matching provides significant improvements in accuracy, consistency, and efficiency. To ensure successful clinical adoption, attention must be given to overcoming financial, data-related, and ethical barriers.